Preparation of bulk sodium carboxymethyl cellulose aerogels with tunable morphology. (15th March 2015) - Lin, Runjun; Li, Ang; Lu, Lingbin; Cao, Yang
Highlights: Bulk carboxymethyl cellulose aerogels with low density and high porosity were obtained by a novel and facile process. By adjusting the mass fraction of Fe 3+, granular, three-dimensional network and rod-like morphology were obtained, in reflection of different coordination numbers, responding to the profile of SEM. With the addition of Fe 3+, the crystal degree and thermal stability were decreased, because of both the coordination between iron ion and carboxylate ion and iron ions penetrated into crystal lattice. Abstract: Homogeneous and bulk carboxymethyl cellulose hydrogel and aerogel were prepared by a novel process, using Fe 3+ andd -(+)-gluconic acid-lactone as cross-linker and releasing agent, respectively. The results showed that the mass fraction of Fe 3+ has a great effect on CMC aerogels' structure, crystallization and morphology. By adjusting the mass fraction of Fe 3+, granular, three-dimensional network and rod-like morphology were obtained, responding to varying density and porosity. The aerogel had low density (low to 0.0568 g/cm 3 ) and high porosity (up to 90.45%). Meantime. Combination patterns between carboxylate ion and iron ion were checked by FTIR. Furthermore, with the addition of Fe 3+, lattice mismatch of CMC emerged and led to decreasing crystalline degree and thermal stability. This work would play an important role in the handy and extensive application of CMC aerogels